2016
DOI: 10.4103/1596-3519.158524
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum leptin and insulin resistance among obese Nigerian women

Abstract: Background:Leptin is a hormone produced directly from adipocytes and has been associated with type 2 diabetes mellitus (T2DM) which is characterized by insulin resistance (IR). Due to the increasing prevalence of obesity in sub-Saharan Africa, serum leptin can be explored as a predictive risk factor for T2DM. Therefore, the aim of this study was to determine the relationship between serum leptin and IR among obese women.Methods:This was a cross-sectional study of obese, adult Nigerian females. Participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
6
31
2
5
Order By: Relevance
“…At the same time, there are publications showing that prolonged hyperleptinemia inhibits the expression of insulin mRNA, which may ultimately serve as a trigger of hyperglycemia and IR 24 . Osegbe et al (2016) have found a positive correlation between the level of leptin and the severity of IR in females with different BMI values 25 . Leptin may also inhibit insulin receptor signal through activation of the suppressor of cytokine signal type 3 26 .…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, there are publications showing that prolonged hyperleptinemia inhibits the expression of insulin mRNA, which may ultimately serve as a trigger of hyperglycemia and IR 24 . Osegbe et al (2016) have found a positive correlation between the level of leptin and the severity of IR in females with different BMI values 25 . Leptin may also inhibit insulin receptor signal through activation of the suppressor of cytokine signal type 3 26 .…”
Section: Discussionmentioning
confidence: 98%
“…As inflammation induces central leptin resistance, leptin is an important link between obesity and HPG axis defects [137]. Interestingly, serum leptin levels are positively correlated with insulin resistance (IR) [138] raising the possibility that leptin is also involved in regulating IR. Indeed, leptin regulates insulin receptor substrate-1 and 2 (IRS-1, IRS2) [139], modulates glucose metabolism and the function of insulin producing pancreatic β-cells [140].…”
Section: Pathophysiological Consequences: Effect Of Obesity-induced Imentioning
confidence: 99%
“…Leptin is called a "satiety hormone" because it regulates food intake and energy expenditure. It acts via leptin receptors which are found in the hypothalamus [1,21]. Its secretion is regulated, among others, by insulin and cortisol concentrations [22].…”
Section: Adipokines -Leptin and Adiponectinmentioning
confidence: 99%